Accounting disclosure of green bonds as a tool for achieving sustainable development: an exploratory study - Belhaj إياد (Journal of Pure & Applied Sciences, 2022)
The accounting disclosure about the elements of sustainable development in general has received great attention from academic researchers, with the increasing interest in the dimensions of sustainable development SD. Previous literature, whether international or local, provided valuable insights into the significant role that accounting disclosure plays on economic, social, and environmental performance in achieving the Sustainable Development Goals (SDGs), but the accounting disclosure of green bonds has been neglected in research, and considering that green bonds are One of the modern practices of sustainable development, the current study responded to this research gap, as it aims to identify the role played by the accounting disclosure of green bonds in achieving sustainable development. The study used the integration of the inductive method, the deductive method, the historical method, and the descriptive method. The basic data were collected by means of a questionnaire specially developed for the purpose of the study. After analyzing the statistical data for (24) responses collected from accountants working at Al Yaqin Bank, the results showed a positive trend about the role played by the accounting disclosure of green bonds in achieving sustainable development. The accounting disclosure of green bonds has a positive role in improving the bank’s financing policy to support sustainable development, and assisting it in deciding the continuity of financing to support environmental projects, and it also achieves the bank’s profitability and contributes to improving its performance. The study extracted a proposed model that enables banks in general to make more effective decisions about issuing green bonds with the aim of serving the environment and the sustainable development. This model was based on the knowledge of the issuer of green bonds on four basic factors that must be made available to the beneficiary organization (the environmental orientation of the organization, its previous activities in supporting of the environment, its future plans, and its study for the employment of green finance).